Cross-Sectional Analysis of Nutritional Status, Knowledge and Uptake of Nutritional Services Among Adolescent Girls in Western India - Saha S; Pandya A; Kandre Y; Raval D; Saxena D (Dove Medical Press, 2021)
Somen Saha,1 Apurvakumar Pandya,2 Yogini Kandre,1 Devang Raval,1 Deepak Saxena1 1Department of Public Health, Indian Institute of Public Health, Gandhinagar, Gujarat, India; 2Parul Institute of Public Health, Parul University, Vadodara, Gujarat, IndiaCorrespondence: Somen SahaDepartment of Public Health, Indian Institute of Public Health, Opp. Air Force Headquarter, Gandhinagar-Chiloda Highway, Near Lekawada Bus Stop, Gandhinagar, Gujarat, IndiaTel +91-968-7207549Email ssaha@iiphg.orgPurpose: Malnutrition status of adolescent girls remains a major public health problem in India. The present study assessed nutritional status, associated factors contributing to malnutrition and their access to health-care services in Dev Bhumi Dwarka district of Gujarat situated in western part of India.Materials and Methods: The study was carried out using descriptive cross-sectional design. A total of 1252 adolescent girls from all four blocks of Dev Bhumi Dwarka district were interviewed by field investigators. The data were collected on socio-demographic characteristics, physical activities, diet, and anthropometry. The WHO classification for body mass index (BMI) was used to assess underweight, overweight, and obesity among adolescent girls. Chi-square analyses were performed to identify significant determinants of under-nutrition.Results: Mean age of the study population was 13.82± 2.31. Of the total, around 34% of the adolescent girls were out-of-school. The prevalence of underweight (